2024
DOI: 10.4103/jpbs.jpbs_1019_23
|View full text |Cite
|
Sign up to set email alerts
|

Perceptiveness and Attitude on the use of Artificial Intelligence (AI) in Dentistry among Dentists and Non-Dentists - A Regional Survey

A. Jebilla Pringle,
V. Kumaran,
Mary Sheloni Missier
et al.

Abstract: Artificial intelligence (AI) is an emerging tool in modern medicine and the digital world. AI can help dentists diagnose oral diseases, design treatment plans, monitor patient progress and automate administrative tasks. The aim of this study is to evaluate the perception and attitude on use of artificial intelligence in dentistry for diagnosis and treatment planning among dentists and non-dentists’ population of south Tamil Nadu region in India. Materials and Methods: A cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(35 reference statements)
1
0
0
Order By: Relevance
“…2 ), more than 75 % of the participants believe that AI can be a useful tool in diagnosis and treatment planning and can revolutionize dentistry in general. This is in agreement with the study by Jebilla et al 16 where in the participating dentist suggested the use of AI as an adjunct in diagnosis and treatment planning. 72 % perceive AI as a partner rather than a competitor in the foreseeable future of dentistry.…”
Section: Discussionsupporting
confidence: 93%
“…2 ), more than 75 % of the participants believe that AI can be a useful tool in diagnosis and treatment planning and can revolutionize dentistry in general. This is in agreement with the study by Jebilla et al 16 where in the participating dentist suggested the use of AI as an adjunct in diagnosis and treatment planning. 72 % perceive AI as a partner rather than a competitor in the foreseeable future of dentistry.…”
Section: Discussionsupporting
confidence: 93%